Key Ratios Analysis between Conventional and Islamic Banking in Bangladesh - Siddiqua, Ayesha; Chowdhury, A. N. M. Minhajul Haque; Siddikee, Md. Jahangir Alam; Chowdhury, Abu Sayed Md. Mahmudul Haque; Parvin, Shahnaz (Global Disclosure of Economics and Business, 2016)
The proliferation of banking sector is an indicator of economic growth in Bangladesh. Conventional Banks as well as the Islamic Banks significantly influence the national economy although there are a number of dissimilarities between the two banking systems. This study was carried out to identify the differences of Conventional and Islamic Banking sectors in terms of ratio analysis. A total of 10 banks in which 5 Conventional and 5 Islamic banks were selected for the study. Some key financial ratios were being used for the analysis. It is found from the study that the Conventional and Islamic Banks had much influence on the national economy as they hold the deposit of general public and invest the funds in profitable projects. The earnings per share (EPS), return on asset (ROA), return on equity (ROE) and return on capital employed (ROCE) were greater in Islamic Banks. It clearly indicates that the Islamic Banks were more profitable and performing a good job in the context of Bangladesh although people preferred Conventional Banking most. JEL Classification Code: G 21